Job Insecurity, Work Stress, Work Family Conflict, and Employees Turnover Intention - Ratnaningrum Ratnaningrum; Tri Purwadi; Heni Susilowati; Titin Hargyatni; Dewi Widyaningsih (Cita konsultindo, 2023)
An employee's willingness to willingly and permanently leave an organization is known as turnover intention. A high degree of willingness to change employment implies that the company is having difficulty retaining staff. An overwhelming workload, poor teamwork, and pressure from superiors may all cause stress in employees. Job insecurity is one reason that might lead to a desire to change jobs. Significant work-family conflict can be resolved by leaving your job, according to some employees. This study aims to examine the influence of job insecurity, work stress, and work family conflict to turnover intention in PT. Raja Roti Cemerlang Bekasi. The study employed a cross-sectional survey design. Data from 60 respondents are collected using simple random sampling and analyzed using a regression model to test the hypotheses developed. The results show that job stress, job insecurity have a positive effect, while work-family conflict has no effect on turn over intention. The research has important implications for knowledge managers knowledgesince it shows that increasing workplace stress and job instability would increase workers' intentions to quit their jobs